Pengaruh Budaya Digital Terhadap Kinerja Karyawan di PT. Fokus Ritel Nusaprima Palembang - Putri, Shinta Nadya; Fauziah Afriyani; Muhammad Bahrul Ulum (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2024)
This study aims to determine the effect of digital culture on the performance of employees of PT Focus Retail Nusaprima. This study uses quantitative research methods with data collection techniques through observation and questionnaire distribution. Sampling in this study using saturated sampling technique. The population in this study were 50 employees of PT Fokus Retail Nusaprima. The analytical tools used in this study are validity test, realibilats test, classical assumption test, simple linear regression test, t-test and hypothesis testing which are analyzed using the help of the SPSS version 27 program. The results of this study indicate that digital culture has a significant positive effect of 26.0%. This is evidenced by the t-count> t-table value, namely (4.102> 2.010) with a significance of 0.00 <0.05. Companies should be able to continue to maintain and optimize the quality of these two things. In order to continue to improve employee and company performance. The results of descriptive analysis show that what needs to be improved in digital culture is the components that must be considered, namely agility and flexibility.